Background voltage distortion and percentage of nonlinear load impacts on the harmonics produced by a group of personal computers - Rawa, M.J.H.; Thomas, David W.P.; Sumner, M. (2014)
The penetration of nonlinear loads on power systems increases distortion levels and can cause severe problems to power systems. Many factors affect the degree of generated harmonics including the background voltage distortion and percentage of nonlinear load to the total load. Hence, the purpose of this paper is to investigate and accurately quantify the effects of these two factors on the harmonics produced by a group of Personal Computers (PCs). Experimental measurements and computer simulations are performed to confirm the observations.